Systematic review of COVID‐19 in children shows milder cases and a better prognosis than adults - Ludvigsson, Jonas F. (Acta Paediatrica, 2020)
Aim The coronavirus disease 2019 (COVID‐19) pandemic has affected hundreds of thousands of people. Data on symptoms and prognosis in children are rare. Methods A systematic literature review was carried out to identify papers on COVID‐19, which is caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), using the MEDLINE and Embase databases between January 1 and March 18, 2020. Results The search identified 45 relevant scientific papers and letters. The review showed that children have so far accounted for 1%‐5% of diagnosed COVID‐19 cases, they often have milder disease than adults and deaths have been extremely rare. Diagnostic findings have been similar to adults, with fever and respiratory symptoms being prevalent, but fewer children seem to have developed severe pneumonia. Elevated inflammatory markers were less common in children, and lymphocytopenia seemed rare. Newborn infants have developed symptomatic COVID‐19, but evidence of vertical intrauterine transmission was scarce. Suggested treatment included providing oxygen, inhalations, nutritional support and maintaining fluids and electrolyte balances. Conclusions The coronavirus disease 2019 has occurred in children, but they seemed to have a milder disease course and better prognosis than adults. Deaths were extremely rare.